Relationship between Neutrophil-Lymphocyte Ratio and Cardiac Autonomic Neuropathy in Diabetes Mellitus Type 2 Patients - Cahyandari Nurlaelatiningsih; Sunaryo Sastradimaja Barki Sastradimaja; Irma Ruslina Defi (International Journal of Integrated Health Sciences, 2017)
Objective: To analyze the correlation between cardiac autonomic neuropathy (CAN) and neutrophil-lymphocyte ratio (NLR) in DM type 2 patients.Methods: This was a cross-sectional study which was conducted at the Internal Medicine Clinic of Dr. Hasan Sadikin General Hospital, Bandung and Chronic Disease Management (CDM) Club in Garut District, West Java, Indonesia from October to December 2015. Subjects were 57 DM type 2 patients who met the inclusion criteria. Cardiac autonomic neuropathy examination and complete blood count (CBC) were performed to discover the subjects’ neutrophil-lymphocyte ratio. Results: A strong correlation was found between CAN in DM type 2 patients and NLR (r=0.679; p=0.000) based on Rank Spearman correlation test. The NLR to CAN cut off point was 1.34. Conclusions: NLR examination can be used as an indicator of CAN in DM type 2 patients with NLR cut off point. There was a correlation between CAN and DM type 2 diagnosis duration. Keywords: Cardiac autonomic neuropathy, diabetes mellitus type 2, Ewing test, neutrophil-lymphocyte ratio DOI: 10.15850/ijihs.v5n1.961